A yeast TCP-1-like protein is required for actin function in vivo. - Vinh, D B (1994)
We previously identified the ANC2 gene in a screen for mutations that enhance the defects caused by yeast actin mutations. Here we report that ANC2 is an essential gene that encodes a member of the TCP-1 family. TCP-1-related proteins are subunits of cytosolic heteromeric protein complexes referred to as chaperonins. These complexes can bind to newly synthesized actin and tubulin in vitro and can convert these proteins into an assembly-competent state. We show that anc2-1 mutants contain abnormal and disorganized actin structures, are defective in cellular morphogenesis, and are hypersensitive to the microtubule inhibitor benomyl. Furthermore, overexpression of wild-type Anc2p ameliorates defects in actin organization and cell growth caused by actin overproduction. Mutations in BIN2 and BIN3, two other genes that encode TCP-1-like proteins, also enhance the phenotypes of actin mutants. Taken together, these findings demonstrate that TCP-1-like proteins are required for actin and tubulin function in vivo.